2019
DOI: 10.1108/aia-09-2018-0035
|View full text |Cite
|
Sign up to set email alerts
|

Autistic women’s experience of intimate relationships: the impact of an adult diagnosis

Abstract: Purpose The purpose of this paper is to explore the experience of intimate relationships of women who have been diagnosed with Autism in adulthood. Design/methodology/approach Semi-structured interviews were used to interview eight participants. The data were transcribed and analysed using the interpretative phenomenological analysis method. Findings Four overall themes were identified. These included “Response to the diagnosis and receiving more information about Autism”, “Factors influencing dating behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Interviews suggested that autistic people might lack the knowledge needed to make empowered health decisions during menopause and that many struggle alone. As well as highlighting unmet support needs around menopause (particularly for accessible information), our data corroborate the importance of helping people process the shame, shock, depression, and anger that might accompany a new, often highly stigmatized diagnosis (Kock, Strydom, O'Brady, & Tantam, 2019;Leedham et al, 2019). The new awareness of their 'normality' within an autistic identity could, however, transform self-criticism into self-compassion, resonant of previous studies around late diagnosis (Bargiela et al, 2016;Kanfiszer, Davies, & Collins, 2017;Kock et al, 2019;Leedham et al, 2019;Milner et al, 2019;Tan, 2018).…”
Section: Discussionsupporting
confidence: 80%
“…Interviews suggested that autistic people might lack the knowledge needed to make empowered health decisions during menopause and that many struggle alone. As well as highlighting unmet support needs around menopause (particularly for accessible information), our data corroborate the importance of helping people process the shame, shock, depression, and anger that might accompany a new, often highly stigmatized diagnosis (Kock, Strydom, O'Brady, & Tantam, 2019;Leedham et al, 2019). The new awareness of their 'normality' within an autistic identity could, however, transform self-criticism into self-compassion, resonant of previous studies around late diagnosis (Bargiela et al, 2016;Kanfiszer, Davies, & Collins, 2017;Kock et al, 2019;Leedham et al, 2019;Milner et al, 2019;Tan, 2018).…”
Section: Discussionsupporting
confidence: 80%
“…Notably, some adults described positive consequences of burnout, especially if it preceded an autism diagnosis, the benefits of which have been reported previously. 19,46,47 Late diagnosis helped the adults in our study find the autistic community, form a positive autistic identity, implement positive career and lifestyle changes, improve self-esteem, and increase confidence to self-advocate for accommodations. This finding highlights the importance of early diagnosis and teaching autistic children effective coping mechanisms (especially during key transition stages) to circumvent the burnout cycle before it begins.…”
Section: Discussionmentioning
confidence: 85%
“…Although many women report relief and positive feelings at diagnosis, identity can be negatively impacted due to self-doubt and feelings of grief for autistic women. 13 However, this study also found that many women report a positive impact of diagnosis on their identity, due to an increase in self-acceptance and self-reflection post-diagnosis. This can in turn have a positive impact on their well-being due to an increased understanding of themselves, their behaviours, and their interpersonal relationships.…”
Section: Introductionmentioning
confidence: 52%